IMAN DAN KARAKTER RELIGIUS PADA ANAK PRASEKOLAH PROGRAM TAHFIDZ DI INDONESIA - Shin Prathiwi; Amir Syamsudin (JP : JURNAL PENDIDIKAN, 2020)
Abstract: The article discusses the interrelationship between the theory of faith development and the formation of children's characters in preschool tahfidz programs. During this time the faith is considered related to human develop-ment, including child development. This assumption has an impact on the rampant standing condition of religious-preschoolers with excellent programs memorizing the holy books in Indonesia. The program of memorizing the Qur'an for Muslims is called tahfidz. The preschool implementation of the Tahfidz program starts from memorizing juz 30th. This educational program was establis-hed in the hope of supporting preserving the Qur'an from the non-written aspect because it is believed to study the Qur'an more first and center of knowledge. In addition, the Qur'an contains guidance on Muslim values and is used as a shaper of religi-ous character. This is related to the meaning of character as the application of values in individual actions. Based on several research results, the hope of preservation of the Qur'an in the Tahfidz program of children is achieved and adds evidence of the relationship of faith with religious character, especially in early childhood. This article is revie-wed by the method of review of literature related topics to reveal conditions in the field.Keywords: Early child; religius character; tahfidz program.